Risk of Using Capillary Active Interior Insulation in a Cold Climate - David Antolinc (MDPI AG, 2021)
The retrofitting of cultural heritage buildings for energy efficiency often requires the internal thermal insulation of external walls. Most of the in situ studies of capillary active interior insulation were performed in mild oceanic climate regions, and they showed an excellent performance. However, as a large part of Central–Eastern Europe belongs to a continental climate with cold winters and long periods of temperatures below the freezing temperature, the applicability of the capillary active interior insulation in cold climate was studied. The hydrothermal behaviour of the three walls was determined—each consists of one of three different interior insulations—and the original wall is made of historic regular solid bricks. Two interior thermal insulations were capillary active (aerated cellular concrete, calcium silicate) and one vapour-tight (glass foam). A hot box–cold box experiment and a steady-state model were used to demonstrate an increase in the original wall mass due to the water condensation only when the capillary active interior insulation is used. The combination of the water condensation and the low sub-zero temperature may lead to a risk of freeze–thaw damage to the original wall. The numerical simulation of the water vapour condensation for the considered walls for the Slovenian town Bled with sub-zero average winter temperatures was performed to obtain the whole temperature and moisture profile. It showed good agreement between an experimentally and numerically obtained amount of water condensation. The capillary active interior insulation proved to be unsuitable for improving the thermal insulation of buildings in cold continental climate, and only a vapour-tight system can be recommended.